Dual Inhibition of Ornithine Decarboxylase and A1 Adenosine Receptor Efficiently Suppresses Breast Tumor Cells - Ma, Hongyan; Li, Qizhang; Wang, Jing; Pan, Jing; Su, Zhengding; Liu, Sen (Frontiers in Oncology, 2021)
The personized treatment of breast cancer is still challenge, and it is of great value to develop more options for treating breast cancer. Combination therapy has been a highly appreciated strategy for breast cancer treatment in recent years, and new combination therapy protocols will be valuable for the treatment of breast cancer. Adenosine and polyamines are both endogenous metabolites with indispensable biological functions. Adenosine binds with A1 adenosine receptor (A1AR) to downregulate cAMP concentration, and both low cAMP content and high polyamine level stimulate the growth and proliferation of cancer cells. In this work, we firstly used a polyamine synthesis inhibitor, DFMO (α-difluoromethylornithine), and an A1AR inhibitor, DPCPX (8-cyclopentyl-1,3-dipropylxanthine) to investigate if simultaneously inhibiting A1AR and polyamine synthesis has synergistical antitumor effects. Then we presented a dual inhibitor (ODC-MPI-2) of A1AR and ODC (ornithine decarboxylase 1), the rate-limiting enzyme in polyamine biosynthesis. We investigated if ODC-MPI-2 could inhibit the proliferation and growth of breast cancer cells. Our data showed that DFMO and DPCPX synergistically inhibit the growth and proliferation of MCF-7 cells. We also demonstrated that ODC-MPI-2 reduces cellular polyamine level and elevates cAMP concentration. We further showed that ODC-MPI-2 inhibits the growth, proliferation, and migration/invasion of MCF-7 cells. Finally, ODC-MPI-2 showed preference on inhibiting triple-negative breast cancer cells. The dual inhibition of ODC and A1AR is a new combination therapy strategy for treating breast cancer, and the dual inhibitors of ODC and A1AR might be effective drugs for treating breast cancer.